Rural Labour Markets and Migration in South Asia: Evidence from India and Bangladesh - Deshingkar, Priya; Farrington, John (Washington, DC: World Bank, 2012)
The question of how rural labour markets and migration can be made to work better for poverty reduction is the focus of the paper. Using select case and longitudinal studies from five parts of India and Bangladesh, the key processes that shape rural labour markets and how these have evolved over time with the changing macro-economic, policy, agro-ecological and infrastructural context are discussed. The authors find that, while agricultural wages have remained relatively low, a few rural labouring households have been able to break out of poverty through household diversification strategies that use a combination of two or more of the following: accessing regular work (not necessarily well-paid) inside or outside the village; leasing in land or being given a land by a patron for cultivating; and starting up a small business. The evidence highlights the complexity of household labour allocation strategies and why analyses based on national statistics alone are not able to capture them.